Visualization Research on Scientific and Technological Information of Aviation Industry in Shaanxi Province - Wang Peng (E3S Web of Conferences, 2020)
The integration of industry and information is necessary for the development of industrial modernization in China. Under the context of this, the research on visualization has leaded to a wide and further integration between science and technology and arts disciplines. It fosters the progress and innovation of digitalization and smart technologies, working to make industrial manufacturing more informationalized. Besides, it has a long-term gaining effect on the digitalization and informatization of relevant national science and technology projects under way and enterprises, and even the development of education, Thus, this paper, based on the progress of aviation industry, combines visual simulation design, visual management system and visual technologies, analyses main methods and key objectives, and elaborates on the effect and significance of integration between visual technologies and manufacturing. Fund program: Special Scientific Research Program of Education Department of Shaanxi(20JK0240)